Examining the Advantages and Disadvantages of Laparoscopic Versus Traditional Open Surgeries in Terms of Recovery, Complication Rates, and Long-Term Outcomes - Mehmood, Yasir; Bashir, Amna; Hussain, Zeeshan; Sulaiman, Muhammad; Gul, Hassam; Ali, Mansab (Indus Journal of Bioscience Research, 2025)
This study compared laparoscopic and open surgeries in terms of recovery time, postoperative complications, and long-term outcomes, including survival rates, recurrence, and quality of life. A total of 140 participants from urban and rural hospitals in Punjab, Pakistan, were studied using a quantitative approach with probability sampling. Data analysis involved descriptive statistics and inferential tests, including t-tests and Log-Rank tests. Results showed that laparoscopic surgery significantly reduced hospital stay (2.5 vs. 5.5 days) and time to resume normal activities (7.2 vs. 12.1 days) compared to open surgery. It also led to fewer complications, such as lower infection rates and improved wound healing. Long-term outcomes indicated slightly higher survival rates (90% vs. 85%) and lower recurrence rates (10% vs. 18%) for laparoscopic procedures, though these differences were not statistically significant. However, quality-of-life assessments favored laparoscopic surgery. Overall, the findings confirm that laparoscopic surgery offers faster recovery, fewer complications, and better postoperative well-being. While survival and recurrence rates remained similar, minimally invasive procedures resulted in greater patient satisfaction. As surgical techniques advance, further research is needed to evaluate their effectiveness in complex cases like advanced cancers and extensive abdominal surgeries. This study highlights the benefits of laparoscopic surgery over open surgery, including faster recovery, fewer complications, and better long-term quality of life. While survival and recurrence rates were similar, the lower complication rates make laparoscopic surgery a preferred choice. Future research should explore its use in complex cases and assess cost-effectiveness. Advancing techniques and standardized training programs will further enhance patient outcomes and influence healthcare policies.